Association of Intact dupA (dupA1) rather than dupA1 cluster with duodenal ulcer in Indian population - Alam, Jawed (Gut Pathog, 2015)
BACKGROUND: The duodenal ulcer promoting gene (dupA) and dupA cluster in Helicobacter pylori have been described as a risk factor for duodenal ulcer development in some populations. Polymorphic gene dupA can be divided into two groups, intact dupA1 (long or short type based on the presence or absence of 615-bp extra sequences at the 5′ region) having complete reading frame and other truncated dupA2 having frame-shift mutation. This study was aimed to elucidate the role of dupA of H. pylori and their clusters in the disease manifestation of Indian population. METHODS: A total of 170 H. pylori strains were screened for the presence of dupA, dupA alleles and dupA cluster by PCR and sequencing. Pro-inflammatory cytokine (IL-8) with different dupA variant H. pylori stimulated gastric epithelial cells (AGS cells) was measured by ELISA. RESULTS: A total of 50 strains (29.4%) were positive for dupA among the tested 170 strains. The prevalence of dupA1 in duodenal ulcer (DU) and non-ulcer dyspepsia (NUD) populations was found to be 25.5% (25/98) and 11.1% (8/72), respectively and 16.4% (28/170) of the tested strains had dupA1, cagA and vacAs1m1 positive. The distribution of long and short type dupA1 has not been significantly associated with the disease outcome. The dupA cluster analysis showed that 10.2% (10/98) and 8.3% (6/72) strains were positive among DU and NUD, respectively. IL-8 production was significantly higher in dupA1(+), cagA(+), vacA(+) (902.5 ± 79.01 pg/mL) than dupA2(+), cagA(+), vacA(+) (536.0 ± 100.4 pg/mL, P = 0.008) and dupA(−), cagA(+), vacA(+) (549.7 ± 104.1 pg/mL, P = 0.009). Phylogenetic analysis of dupA indicated that the Indian H. pylori strains clustered with East Asian strains but distinct from Western strains. This is the first known genetic element of Indian H. pylori that is genetically closer to the East Asian strains but differed from the Western strains. CONCLUSIONS: The intact dupA1 was significantly associated with DU than NUD (P = 0.029) but the dupA1 cluster has no role in the disease manifestation at India (P = 0.79). Thus, dupA1 can be considered as a biomarker for DU patients in India.